The experimental modelling of stress urinary incontinence - Iatsyna, O. I.; Vastyanov, R. S.; Savytska, I. M.; Vernygorodskyi, S. V. (Journal of Education, Health and Sport, 2018)
The stress urinary incontinence (SUI), especially in women, constitutes most frequent complication of urogynecological diseases. Adequate and a stable reproducible model of SUI in white laboratory rats was created, using bilateral ligature of pudendal nerves. This guarantees a stable signs of SUI, which had progressed while the experiment duration enhanced. In accordance to the urodynamical investigations data, the leak pressure of the urine first drop in operated laboratory animals was registered; results of histological and morphometric investigations had witnessed about the ureter’s diameter enhancement and the muscles tone lowering. In accordance to the investigation data, the ureter’s and its sphincter denervation was stable, and the model application had permitted to obtain stable reproducible results. The received model meets the requirements for qualitative indicators in the study of morphological changes in hyperactive urinary bladder model and can be used as a basis in the preclinical stage of research. The results of pathomorphological studies with revealed peculiarities of rearrangement of collagen fibers, degenerative changes of the elastic in the target organ, taking into account the anatomic-functional orientation of action, form the basis for further clarification of the mechanisms of occurrence and determination of the SUI recurrence.